Сравнительный анализ потерь активной мощности асинхронных двигателей с цилиндрическим и аксиальным рабочим зазором - Ставинский, Андрей Андреевич; Пальчиков, Олег Олегович (НТУ "ХПИ", 2015)
На основе метода показателей технического уровня с относительными управляемыми переменными получены аналитические зависимости определения оптимальных геометрических соотношений активной части торцевого асинхронного двигателя с короткозамкнутым ротором по критерию минимума потерь и выполнен сравнительный анализ показателей потерь активной мощности электромагнитно-эквивалентных двигателей классического цилиндрического и аксиального исполнений.

Purpose.To find the analytical expressions of determining the optimum geometric dimensions by criteria of the losses minimum of axial field squirrel-cage induction motors and to compare traditional and axial field motors. Methodology. We have applied the method of the relative indications of the technical level with relative controlled variables. We have used the approximation of the experimental dependence of the distribution of the induction in the air gap and the integral averaging of the magnetic flux. Results. We have developed the mathematical model for determining the optimum geometric dimensions by criteria of the losses minimum of the active part of axial field squirrel-cage induction motors taking into account the radial distribution of the induction in the air gap and teeth. We have considered the comparative analysis of the indications of active power losses of traditional and axial designs of electromagnetic equivalent motors. Originality. For the first time we have created the mathematical model of the active power losses of the active part of axial field squirrel-cage induction motors with the uneven distribution of the magnetic flux in the core and investigated the effect of the geometric relationships on the energy efficiency of axial field motors. Practical value. Based on the superior parametric compatibility and the high energy efficiency of axial motors the expediency of replacing traditional induction motors to axial field induction motors has been proved in the special drives, which operates in continuous duty. Also obtained by simulation optimal geometric relationships of the magnetic circuit can be used in the manufacture and design of axial motors by criteria of the losses minimum.
Comparative analysis of active power losses of induction motors with cylindrical and axial air gaps
Keywords: ротор; статор; система электромагнитная; сопротивление обмотки; losses indication; optimum geometric dimensions; traditional field motors; axial field motors